(untitled) (Far Eastern Federal University: School of Engineering Bulletin, 2025)
Innovative honeycomb structures have attracted significant attention from researchers in recent years due to their unique mechanical properties and special characteristics. The article presents key foreign publications containing striking examples of research in the field of honeycomb structures, and provides a fairly broad overview of achievements in the development of innovative honeycomb structures over the past twenty years, covering the topics of filling, integration, structures with a negative Poisson ratio, etc. It examines the main mechanical properties of these structures, identifies their strengths and weaknesses based on geometry, mechanical parameters, and dynamic responses. Analysis of literature sources has highlighted current challenges and outlined potential directions for future research. The conclusions offer valuable recommendations for further investigation and design of lightweight, robust span structures using cellular configurations.To deepen understanding of the behavior of cellular structures, additional studies are needed on analogous elements and full-scale structural samples.